Maternal Childhood Maltreatment, Internal Working Models, and Perinatal Substance Use: Is There a Role for Hyperkatifeia? A Systematic Review - Aviva K. Olsavsky; Isabella Chirico; Diab Ali; Hannah Christensen; Brianna Boggs; Lillian Svete; Katherine Ketcham; Kent Hutchison; Charles Zeanah; Nim Tottenham; Paula Riggs; C. Neill Epperson (SAGE Publishing, 2023)
The parent-infant relationship is critical for socioemotional development and is adversely impacted by perinatal substance use. This systematic review posits that the mechanisms underlying these risks to mother-infant relationships center on 3 primary processes: (1) mothers' childhood maltreatment experiences; (2) attachment styles and consequent internal working models of interpersonal relationships; and (3) perinatal substance use. Further, the review considers the role of hyperkatifeia, or hypersensitivity to negative affect which occurs when people with substance use disorders are not using substances, and which drives the negative reinforcement in addiction. The authors performed a systematic review of articles (published 2000-2022) related to these constructs and their impact on mother-infant relationships and offspring outcomes, including original clinical research articles addressing relationships between these constructs, and excluding case studies, reviews, non-human animal studies, intervention studies, studies with fewer than 30% female-sex participants, clinical guidelines, studies limited to obstetric outcomes, mechanistic/biological studies, and studies with methodological issues precluding interpretation. Overall 1844 articles were screened, 377 were selected for full text review, and data were extracted from 157 articles. Results revealed strong relationships between mothers' childhood maltreatment experiences, less optimal internal working models, and increased risk for perinatal substance use, and importantly, all of these predictors interacted with hyperkatifeia and exerted a marked impact on mother-infant relationships with less data available on offspring outcomes. These data strongly support the need for future studies addressing the additive impact of maternal childhood maltreatment experiences, suboptimal internal working models, and perinatal substance use, with hyperkatifeia as a potential moderator, and their interacting effects on mother-infant socioemotional outcomes.